Schematizing Societal Problems in Namibian Novels: The Cases of The Other Presence and The Hopeless Hopes - Linus Nghilifavali Hafeni; Haileleul Zeleke Woldemariam (Journal of Communication and Cultural Trends, 2022)
The current research presents a cognitive stylistics study of two Namibian novels: Francis Sifiso Nyathi’s The Other Presence and Salom Shilongo’s The Hopeless Hopes. These novels were selected because they present societal problems specific to Namibia from two different perspectives. The study also argues that only a few such Namibian novels have been investigated via conceptualising cognitive stylistics. The researchers have raised three fundamental questions: How does cognitive metaphor help explicate psychological hitches as captured creatively in the two novels? What is the mind’s contribution in conceptualising and comprehending contextual meanings in the two novels? How does content schema contribute to the understanding of the two novels? It is, therefore, against the backdrop of these three questions that the two novels were purposefully selected and studied. Conceptualising and implementing the cognitive metaphor, the current study also analyses the root causes of societal problems, such as unemployment, unfair treatment of people, HIV/AIDS, and witchcrafts, prevailing in the Namibian social fabric. In The Other Presence, it is the HIV/AIDS which is  referred  to  as the other presence. Shilongo’s The Hopeless Hopes also reveals how Robert and the other fellow Namibian ex-combatants gathered at a Big House in Windhoek to hand over their petition to Honourable Zopa. It indicates clearly that the State House is being contextualised as a Big House in the novel, while the ‘Founding Father’ and the former president of the country Honourable Sam Nuyoma is referred to as Honourable Zopa. The contextual meaning of the selected novels can thus only be understood if the readers of these novels have a general background knowledge of the Namibian society. Within a cognitive stylistics theoretical framework, the study also follows a schema theory to explain mental problems and contextual meanings. It manifests how a cognitive stylistics approach to Namibian novels can advance the literary understanding of the multiplicities of themes, such as culture, taboo, superstition, unemployment, colonialism, corruption, and mental health.Keywords: cognitive metaphor, cognitive stylistics, content schema, contextual meanings, mental problems, schema theory